2003
DOI: 10.1080/00016489.2003.11720744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Botulinum Toxin Type A on Nasal Symptoms in Patients with Allergic Rhinitis: A Double-blind, Placebo-controlled Clinical Trial

Abstract: In selected cases, injection of 40 units of BTX-A into the turbinates, as a single agent, may help the symptomatic control of AR for up to 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 14 publications
2
50
0
13
Order By: Relevance
“…The results showed that typical AR symptoms, such as rhinorrhea, nasal itching and sneezing, were relieved following BTX-A treatment. Our study further demonstrated that the severity of rhinorrhea was significantly diminished in the AR + BTX-A group compared with the AR group, being in accordance with the recent exploratory clinical treatment in patients with AR [12] .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results showed that typical AR symptoms, such as rhinorrhea, nasal itching and sneezing, were relieved following BTX-A treatment. Our study further demonstrated that the severity of rhinorrhea was significantly diminished in the AR + BTX-A group compared with the AR group, being in accordance with the recent exploratory clinical treatment in patients with AR [12] .…”
Section: Discussionsupporting
confidence: 74%
“…A recent test of BTX-A in AR patients has demonstrated that BTX-A could relieve rhinorrhea, nasal obstruction and sneezing [12] . BTX-A is well known to inhibit acetylcholine (ACh) release from cholinergic nerves in skeletal muscles [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Allergan, bezogen. In einer Arbeit zeigte sich kein relevanter Unterschied zwischen den Behandlungsgruppen mit jeweils 20 und 30 Einheiten pro Nasenseite [27]. Als eigene klinische Erfahrung ist daher ein individuelles Herantasten der jeweiligen Dosis notwendig, wobei wir bei hö-heren Dosen sowohl injizierten als auch die Schwämmchen einlegten, um den Ablauf in den Nasopharynx bei höheren Volumina zu vermeiden.…”
Section: Introductionunclassified
“…Wie bei den anderen Botulinumtoxinindikationen ist auch hier zu beachten, dass bei fehlender oder zu geringer Wirkung die erneute Behandlung erst nach mehreren Wochen wieder erfolgen sollte, um die immunologischen Boosterphänomene zur Antikörperbil-dung zu reduzieren. Während die nasale Hyper sekretion und der Niesreiz zumeist gut ansprechen, gibt es zur nasalen Obstruktion widersprüchliche Ergebnisse [22,27]. Bei den unterschiedlichen Effekten in den Studien sind die Patientenselektion (allergisch vs. nichtallergisch), Dosierungsmengen und Applikationsformen zu beachten.…”
Section: Introductionunclassified
“…The results were significantly better in patients treated with botulinum toxin, especially in rhinorrhoea, nasal obstruction and sneezing. In selected cases, the injection of intranasal toxin botulinum may help control allergic rhinitis symptoms (Unal et al, 2003).…”
Section: Therapeutic Developments In the Treatment Of Allergic Rhinitmentioning
confidence: 99%